Peran United Nations High Commissioner For Refugees (UNHCR) dalam Menangani Permasalahan Stateless di malaysia - Pristina Widya; Najamuddin Khairur Rijal (Journal of Social and Policy Issues, 2022)
This study discusses the role of the United Nations High Commissioner for Refugees (UNHCR) in dealing with stateless problems in Malaysia from 2014-2017. As an international organization, UNHCR deals with stateless issues, namely people who are not considered citizens by any country according to their legal operations. The research method used is descriptive-qualitative. The results found that UNHCR performed its role as an information provider, law enforcer, and policy implementer. As an information provider, UNHCR carries out the #Ibelong campaign and provides information about its partners. As a rule enforcer, UNHCR encourages Malaysia to ratify the stateless convention and provide legal assistance. As a policy implementer, UNHCR carries out mapping projects and provides funding for stateless programs.